The Effect of People’s Business Credit (Kur) and Qris Utilization on Business Development and Income of Culinary Msmes in Denpasar City - Ni Luh Putu Riska Darmayanti; Ni Made Tisnawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
MSMEs have proven to be a resilient sector in facing various economic crises in Indonesia, including the crisis caused by the COVID-19 pandemic. However, digitalization among MSMEs in Indonesia has not yet yielded significant or tangible results. In addition, MSMEs face numerous challenges in adapting to digital markets, particularly in terms of financing. Therefore, it is essential to identify the factors that influence business development and income, particularly for culinary MSMEs in Denpasar City. This study aims to analyze the effect of People's Business Credit and the use of the QRIS on business development and income, as well as their indirect effects through business development. A quantitative approach was employed in this research, which was conducted on culinary MSMEs in Denpasar City. A total of 99 MSME units were selected using purposive sampling. Data were collected through observation and interviews, and analyzed using path analysis. The results indicate that: (1) KUR and QRIS usage have a direct positive effect on business development; (2) KUR, QRIS usage, and business development have a direct positive effect on the income of culinary MSME actors; and (3) KUR and QRIS usage indirectly influence income significantly through the mediation of business development.